Amphetamine Abuse/Dependence Among Pregnant Women, United States 2003-2014 [20B]. (May 2018) - Admon, Lindsay K.; Kozhimannil, Katy B.; Rowe, Meghan E.; Dalton, Vanessa K.; Winkelman, Tyler
Abstract : INTRODUCTION: Nearly one million individuals in the United States reported using amphetamines in 2015. Particularly high levels of use have been identified among rural populations in the West and Midwest. Our objective was to characterize the incidence and geographic distribution of amphetamine abuse/dependence among women who give birth in the United States. METHODS: We conducted a retrospective, serial cross-sectional analysis using 2003 to 2014 data from the National Inpatient Sample, a nationally representative sample of hospital discharges. The cohort included all obstetric deliveries. Amphetamine abuse/dependence was identified with ICD-9-CM codes 305.7x and 304.4x. Incidence rates were calculated with logistic regression models. RESULTS: Amphetamine use disorders were identified in 16, 469 of 9, 921, 691 unweighted delivery hospitalizations. Maternal amphetamine abuse/dependence reached a nadir in 2009-10 and then increased disproportionately in rural compared to urban counties. Incidence in rural Western, Midwestern, and Southern counties was significantly higher in 2013-14 compared to urban counties in those regions (all P<.001). The highest incidence of amphetamine abuse/dependence was identified among pregnant women living in rural, western counties at 9.6 (95% CI 8.2-11.0) per 1, 000 hospital deliveries in 2013-14. CONCLUSION: Maternal amphetamine abuse/dependence increased in the United States after 2009-10 and disproportionately impacted rural residents and communities in the West. These findings amplify recent calls for policy- and practice-level interventions to facilitate the prevention and treatment of substance use disorders among pregnant women. In contrast to opioid use disorders, evidence-based pharmacologic treatment options for amphetamine abuse/dependence are lacking. Prevention may play a key role in improving outcomes for mothers and their infants.